The effect of scoria, perlite and crumb rubber aggregates on the fresh and mechanical properties of geopolymer concrete. (April 2022) - Hamidi, Fatemeh; Valizadeh, Afsaneh; Aslani, Farhad
Abstract: To broaden the practical applications of the geopolymer concrete (GC) at the same large-scale structural level as the conventional concrete (CC), careful assessment of the fresh and mechanical performance of the new concrete technologies based on the GC binder are essential. Lightweight concrete (LWC) is of significant importance for the seismic-resistant lightweight structures, while rubberised concrete is an innovative structural material to tackle the issues associated with the accumulation of the scrap tires in the environment. Current research makes attempt to develop and characterise the rubberised geopolymer concrete (RGC) using 10-mm recycled crumb rubber (CR) aggregates as substitution for the natural coarse aggregates by 5, 10, 15, and 20% replacement. Lightweight geopolymer concrete (LWGC) utilising lightweight scoria and perlite aggregates as replacement for the natural coarse and fine aggregates, respectively, by 25, 50, 75, and 100% proportions were prepared as well. Thereafter, the RGCs and LWGCs were subjected to the fresh and mechanical properties analysis after 3, 7, and 28 days of ambient-curing. For the RGCs, the obtained results denoted no deterioration of the flowability, improved 7-, and 28-day compressive, tensile, and flexural strengths, and enhanced strain-hardening behaviour comparing to the plain GC. For the LWGCs, the obtained results revealed severe segregation for the mixes containing 25% perlite or more, and high risk of segregation for the mixes containing more than 75% scoria. The results obtained for the mechanical properties of the LWGCs suggested that the scoria content in the range of 25–75% improved the fresh and mechanical properties of LWGC compared with GC. In addition, the RGCs represented superior load-bearing capability rather than the LWGCs.